Assessment of Physicochemical Properties of Rituximab Related to Its Immunomodulatory Activity - Mariana P. Miranda-Hernández; Carlos A. López-Morales; Nancy D. Ramírez-Ibáñez; Nelly Piña-Lara; Nestor O. Pérez; Aarón Molina-Pérez; Jorge Revilla-Beltri; Luis F. Flores-Ortiz; Emilio Medina-Rivero (Journal of Immunology Research)
Rituximab is a chimeric monoclonal antibody employed for the treatment of CD20-positive B-cell non-Hodgkin’s lymphoma, chronic lymphocytic leukemia, rheumatoid arthritis, granulomatosis with polyangiitis and microscopic polyangiitis. It binds specifically to the CD20 antigen expressed on pre-B and consequently on mature B-lymphocytes of both normal and malignant cells, inhibiting their proliferation through apoptosis, CDC, and ADCC mechanisms. The immunomodulatory activity of rituximab is closely related to critical quality attributes that characterize its chemical composition and spatial configuration, which determine the recognition of CD20 and the binding to receptors or factors involved in its effector functions, while regulating the potential immunogenic response. Herein, we present a physicochemical and biological characterization followed by a pharmacodynamics and immunogenicity study to demonstrate comparability between two products containing rituximab. The physicochemical and biological characterization revealed that both products fit within the same response intervals exhibiting the same degree of variability. With regard to clinical response, both products depleted CD20+ B-cells until posttreatment recovery and no meaningful differences were found in their pharmacodynamic profiles. The evaluation of anti-chimeric antibodies did not show differential immunogenicity among products. Overall, these data confirm that similarity of critical quality attributes results in a comparable immunomodulatory activity.